EU banks rating assignments: Is there heterogeneity between new and old member countries? - Guglielmo Maria Caporale; Roman Matousek; Chris Stewart (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We model EU countries' bank ratings using financial variables and allowing for intercept and slope heterogeneity. Our aim is to assess whether old and new EU countries are rated differently and to determine whether new ones are assigned lower ratings, ceteris paribus, than old ones. We find that country-specific factors (in the form of heterogeneous intercepts) are a crucial determinant of ratings. Whilst new EU countries typically have lower ratings than old ones, after controlling for financial variables we also discover that all countries have significantly different intercepts, confirming our prior belief. This intercept heterogeneity suggests that each country's rating is assigned uniquely, after controlling for differences in financial factors, which may reflect differences in country risk and the legal and regulatory framework that banks face (such as foreclosure laws). In addition, we find that ratings may respond differently to the liquidity and operating expenses to operating income variables across countries. Typically ratings are more responsive to the former and less sensitive to the latter for new EU countries compared with old EU countries.
Keywords: C25; C51; C52; G21; 330; EU countries; banks; ratings; ordered probit models; index of indicator variable; Bank; Kreditrisiko; Bewertung; Ratingagentur; Regression; Modell-Spezifikation; EU-Staaten (Osteuropa); EU-Staaten